AKADEMIK LITSEY O‘QUVCHILARINING FUQAROLIK POZITSIYASINI RIVOJLANTIRISHNING PEDAGOGIK MODELI - Orınbetov, N.T. (SCIENCE and SOCIETY, 2024)
This article analyzes the pedagogical model of civic education of young people and the development of their civic position developed by scientists, and talks about the pedagogical model we developed, its quality criteria and main components.